PREVALENCE OF PHLEBITIS RELATED TO THE USE OF PERIPHERAL INTRAVENOUS DEVICES IN CHILDREN - Elessandra Souza Bitencourt; Camila Nunes Leal; Radamés Boostel; Verônica de Azevedo Mazza; Jorge Vinícius Cestari Felix; Edivane Pedrolo (Universidade Federal do Paraná, 2018)
Objective: To assess the prevalence of phlebitis, related to the use of peripheral intravenous devices in children in a teaching hospital. Method: A quantitative, descriptive and retrospective study, based in data taken from the phlebitis notification form related to peripheral intravenous therapy, in June 2011 - June 2014, in a pediatric intensive care unit in the city of Curitiba, in the Brazilian state of Paraná (PR). Results: Of a total of 1306 catheters, 339 cases of phlebitis were notified (prevalence of 26%) in the three-year period. The prevalence of phlebitis was 34% in children aged from 0 to 2 years and was 30.2% (n=179) among female children. Regarding the classification of the cases of phlebitis, 82.6% (n=280) were Grade 1, and the mean dwell-time of the device was 49.92 ± 43.19 hours. Conclusion: The data presented here demonstrate a high prevalence of phlebitis in pediatric patients, and the need to seek measures capable of reducing these events.